Diverse Swards and Mixed-Grazing of Cattle and Sheep for Improved Productivity - Jerrentrup, Jana Sabrina; Komainda, Martin; Seither, Melanie; Cuchillo-Hilario, Mario; Wrage-Mönnig, Nicole; Isselstein, Johannes (Frontiers in Sustainable Food Systems, 2020)
Phytodiversity is suggested to increase primary production of grasslands. However, whether this advantage can be converted into secondary production, i.e. the performance of grazing livestock, remains an open question. Animal production of cattle and sheep can be enhanced by mixed-grazing, but, to our knowledge, this effect has never been studied in relation to phytodiversity. Therefore, a rotational grazing experiment was conducted over five years (2007-2011) on permanent grassland in Germany using sheep and cattle in mono- or mixed-grazing of swards differing in plant species richness. Chemical herbicides against dicotyledonous plant species were used to create different sward types: species-poor grass-dominated swards in contrast to untreated ‘diverse’ control swards. We found no differences in herbage production between the sward types. However, compared to the grass-dominated sward, the diverse sward showed a larger concentration of crude protein and a smaller one of acid detergent fibre in herbage dry-matter. Live weight gains of lamb production was slightly greater on the diverse-swards (P<0.05), while calf performance was unaffected by sward type. Mixed-grazing increased daily average live weight gains of suckler cows (g cow-1 d-1) (P<0.05) as well as area-related daily live weight gains (kg ha-1 d-1) and total live weight gains (kg ha-1) during the complete grazing season (P<0.001), which displays the advantage of combining livestock species due to complementary pasture use. We suggest that mixed-grazing of cattle and sheep on phytodiverse swards is particularly appropriate to enhance ecological and agronomical traits such as livestock production of grassland to improve extensive meat production in a sustainable way. Especially lamb production profited by mixed-grazing with a +17% increase in live weight gain. Compared to the grass-dominated sward, diverse-swards resulted in an average +12%-increase of live weight gains (across grazing systems and livestock species).